Video Storytelling as an Effective Strategy for College Brand Awareness - Rilla Gantino; Desy Apriani; Fanani Islamia Ningrum; Rifqi Fahrudin; Kamal Arif Al-Farouqi; Bintang Nanda Henry (ADI Publisher, 2025)
As digital threats to privacy and data integrity continue to rise, cybersecurity has become a critical issue in the business and financial sectors. However, existing risk mitigation strategies tend to focus primarily on technical aspects, often overlooking the ethical dimensions that are vital for governance and decision-making, especially in the development and implementation of emerging technologies such as Artificial Intelligence (AI). This study aims to explore the role of ethical principles in cybersecurity risk mitigation through a Systematic Literature Review (SLR). A total of eleven relevant articles were analyzed using the SALSA framework (Search, Appraisal, Literature Systems, Analysis). The findings indicate that ethical values such as transparency, accountability, fairness, and compliance with regulations play a significant role in enhancing the effectiveness of cybersecurity strategies. Key challenges identified include the absence of global ethical standards, limited human resources with digital ethics expertise, and ethical dilemmas in the use of AI. This review underscores the necessity of integrating ethical values into organizational policies, technologies, and cultures to establish more sustainable and trustworthy cybersecurity systems.